The predictive power of electronic reporting system utilization on voluntary reporting of near-miss incidents among nurses: A PLS-SEM approach - Mohammed Abdalraheem Alalaween; Noorliza Karia (Belitung Nursing Journal, 2024)
Background: Patient safety is crucial in healthcare, with incident reporting vital for identifying and addressing errors. Near-miss incidents, common yet underreported, serve as red flags requiring attention. Nurses’ underreporting, influenced by views and system usability, inhibits learning opportunities. The Electronic Reporting System (ERS) is a modern solution, but its effectiveness remains unclear. Objective: This study aimed to investigate the role of the ERS in enhancing the voluntary reporting of near-miss (VRNM) incidents among nurses. Methods: A cross-sectional study was conducted in the Al Dhafra region of the United Arab Emirates, involving 247 nurses from six hospitals. Data were collected using a questionnaire between April 2022 and August 2022. Structural Equation Modelling Partial Least Square (SEM-PLS) was employed for data analysis. Results: The average variance extracted for the ERS construct was 0.754, indicating that the common factor accounted for 75.4% of the variation in the ERS scores. The mean ERS score was 4.093, with a standard deviation of 0.680. For VRNM, the mean was 4.104, and the standard deviation was 0.688. There was a positive correlation between ERS utilization and nurses’ willingness to report near-miss incidents. Additionally, our research findings suggest a 66.7% relevance when applied to various hospital settings within the scope of this study. Conclusion: The findings suggest that adopting a user-friendly reporting system and adequate training on the system’s features can increase reporting and improve patient safety. Additionally, these systems should be designed to be operated by nursing staff with minimal obstacles.